Bile Acid Synthesis: From Nature to the Chemical Modification and Synthesis and Their Applications as Drugs and Nutrients - Šarenac, Tanja M.; Mikov, Momir (Frontiers in Pharmacology, 2018)
Bile acids are amphiphilic molecules with 24 carbon atoms, consisting of a hydrophobic and a rigid steroid nucleus, which they are attached a hydrophilic hydroxyl groups and a flexible acidic aliphatic side chain . The steroidal core of bile acids constitutes a saturated cyclopentanoperhydrophenanthrene skeleton, consisting of three six-membered (A, B and C) and one five-membered ring (D). Primary bile acids are produced in the hepatocytes, while secondary bile acids are formed by modifying of primary bile acids in the intestinal lumen, i.e. by the reactions of 7alfa−dehydroxylation and deconjugation of cholic and chenodeoxycholic acid. The most important secondary bile acids are deoxycholic and lithocholic acid. Their effects, bile acids realize through nuclear FXR receptors and membrane TGR5 receptors. It has been found that bile acids are also associated with other receptor-vitamin D receptor (VDR), which the most significant ligand is calcitriol, as well as for the pregnane X receptor (PXR) and potentially for the constitutive androstane receptor (CAR), whose ligands are numerous, structurally different xenobiotics, which are associated with greater affinity for bile acids. Bile acids as absorption promoters have the potential to aid intestinal, buccal, transdermal, ocular, nasal, rectal and pulmonary absorption. Bile acids as therapeutic agents (drugs) have the potential to produce beneficial effects in sexually transmitted diseases, primary biliary cirrhosis, primary sclerosing cholangitis, gallstones, digestive tract diseases, cystic fibrosis and cancer. Ursodeoxycholic acid possesses cholesthetic and antiprotective properties and it is used in the treatment of hepatobiliary symptoms of cystic fibrosis. The ursodeoxocholic acid normalizes the function of the liver, tests and prevents the progression of fibrosis. Bile acids achieve most of their effects by modulating gene expression through nuclear receptors, as a transcription factor. In this paper, the different pathways of bile acid biosynthesis are explained as well as chemical modifications and synthesis of different keto derivatives of bile acids. Also, the effects of bile acids in digestion as nutrients, their role as drugs, and in particular the emphasis on the hypoglycemic properties of 7alfa, 12alfa−dihydroxy−12−keto−5beta−cholanic acid in the treatment of diabetes mellitus were examined in detail.